2012
DOI: 10.1155/2012/405981
|View full text |Cite
|
Sign up to set email alerts
|

Thrombocytopenia as an Indicator of Malaria in Adult Population

Abstract: Objectives. To evaluate the predictive value of thrombocytopenia in malaria. Patients and Methods. It was a prospective observational study on all febrile patients with thrombocytopenia presenting to the Medical Unit of Hayat Abad Medical Complex during November 2008 to November 2010. Results. Of the total of 228 patients with fever and thrombocytopenia, 121 patients (53%) proved to be suffering from malaria. Of them 82 patients (68%) had falciparum malaria while 39 patients (32%) had vivax infection. Of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
43
0
6

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(59 citation statements)
references
References 16 publications
7
43
0
6
Order By: Relevance
“…Also, in this study, very severe cases (grade IV) of thrombocytopenia were not observed while majority of thrombocytopenic patients had mild and moderate thrombocytopenia. This is in line with many previous studies in adults where thrombocytopenia in malaria was generally reported to be mild or moderate which resolved shortly after the malaria was treated successfully [15,16]. Since malaria in this study area is hyperendemic, adults in this locality would usually not come down with severe malaria because of the partial immunity they acquire over the years.…”
Section: Discussionsupporting
confidence: 91%
“…Also, in this study, very severe cases (grade IV) of thrombocytopenia were not observed while majority of thrombocytopenic patients had mild and moderate thrombocytopenia. This is in line with many previous studies in adults where thrombocytopenia in malaria was generally reported to be mild or moderate which resolved shortly after the malaria was treated successfully [15,16]. Since malaria in this study area is hyperendemic, adults in this locality would usually not come down with severe malaria because of the partial immunity they acquire over the years.…”
Section: Discussionsupporting
confidence: 91%
“…Nearly 75% malarial patients had thrombocytopenia (platelet count of less than 150 ×103/uL); these finding are supported by Malik et al [15] and Memon et al [16], who reported that 70% of malarial cases had thrombocytopenia. It is a general consensus that thrombocytopenia is very common in malaria [17,18]. The degree of thrombocytopenia has been considered a criterion of disease severity by David et al in the United Kingdom [19].…”
Section: Discussionmentioning
confidence: 99%
“…5 Another prospective study, which was conducted on 228 patients with fever and thrombocytopenia in medical unit of Hayatabad Medical Complex during 2008 -2010 was showing malaria as the commonest cause (53%), in which 68% were having falciparum malaria. 6 While Modi T et al study 3 and Raikar et al study 7 had viral aetiology as the major cause of febrile thrombocytopenia. Present study reveals that severe thrombocytopenia (Platelet < 20000/mm 3 ) is present in 18% of cases, moderate thrombocytopenia (20000 -50000/mm 3 ) in 34% and mild thrombocytopenia (> 50000/mm 3 ) is present in 48% of cases.…”
Section: Aetiologymentioning
confidence: 97%